2013
DOI: 10.1177/2045125313487548
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanisms for the skeletal effects of antipsychotics in children and adolescents

Abstract: The increasing use of antipsychotics (APs) to treat pediatric psychiatric conditions has led to concerns over the long-term tolerability of these drugs. While the risk of cardiometabolic abnormalities has received most of the attention, preclinical and clinical studies provide preliminary evidence that APs can adversely impact bone metabolism. This would be most concerning in children and adolescents as suboptimal bone accrual during development may lead to increased fracture risk later in life. However, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 122 publications
2
67
0
Order By: Relevance
“…In this study, we hypothesized that RIS causes SNSmediated bone loss (26,31). In brief, we found high energy expenditure (EE) and markers of SNS activity in RIStreated mice, consistent with elevated SNS tone.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In this study, we hypothesized that RIS causes SNSmediated bone loss (26,31). In brief, we found high energy expenditure (EE) and markers of SNS activity in RIStreated mice, consistent with elevated SNS tone.…”
mentioning
confidence: 68%
“…Potential sex differences and other mechanisms through which RIS affects bone (including via prolactin-induced hypogonadism and direct effects bone cells themselves) are currently under investigation. Although the mechanisms whereby RIS activates SNS outflow to bone remain unclear, the role of the SNS in mediating bone loss in humans treated with AA medications should be prospectively examined, particularly because some individuals are concomitantly treated with ␤-blockers (31). Future clinical studies will provide insight into the pathophysiologic consequences of AA treatment and help to inform clinical decision-making about this widely prescribed class of medications.…”
Section: Discussionmentioning
confidence: 97%
“…Many of the participants had taken risperidone and SSRIs (95 and 46%, respectively; Table III). These medications affect bone metabolism, 18, 30 which could have masked an independent effect of psychostimulants. Thus, future studies should consider examining the skeletal effects of psychostimulants in the absence of polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study found that BMD in 120 firstepisode inpatients with schizophrenia prescribed either clozapine, quetiapine or aripiprazole was significantly lower than in matched healthy controls (n=90), 12-months after drug initiation 17 . In pediatric patients, AA-associated fractures were increased 2-3 fold with an associated reduction in bone mass [20][21] . Given the devastating effects of fractures in elderly patient populations, as well as the potential of inhibiting peak bone accrual in pediatric patients, the antipsychotic-induced association with increased fracture risk should impact prescribing practices in vulnerable patient populations.…”
Section: Psychiatric Medications and Bone: Clinical Evidencementioning
confidence: 99%
“…A popular hypothesis in the clinical literature is that the AA-induced increase in fractures is due to hyperprolactinemia induced hypogonadism 20 . It is well known that hypogonadism causes bone loss and increased fracture risk, and antipsychotic medications can cause hyperprolactinemia in women, men and children.…”
Section: Elucidating Underlying Mechanisms: Hyperprolactinemiamentioning
confidence: 99%